To the question of optimizing the volume of experimental studies in justification of the medical and sanitary standard for pesticides in soil (Environment & Health, 2025)
The aim: verification of the reliability of the methodology for optimizing the volume of experimental studies in the substantiation the medical and sanitary standard of the active substance (AS) for plant protection products (PPP) in the soil based on the analysis of the results of laboratory experiments on the study of the migration of pesticides of different chemical classes in the «soil - adjacent environments» system in extreme soil and climatic conditions.Materials and methods. According to the original methodology, the danger of contamination of the surface layer of the atmospheric air due to evaporation from the soil of 7 AS PPP, for which the maximum allowable concentrations in the soil (MPCs) were previously substantiated, was carried out. For this purpose, the risk of the possible inhalation effect of the studied AS on the body of agricultural workers and the population was assessed by determining the preliminary and final integrated hazard indexes (PIHI and FIHI, respectively). The obtained results made it possible to draw conclusions about the expediency of the experimental study of the migration of the studied AS from the soil into the air. To assess the reliability of these conclusions, the threshold concentrations of the investigated AS in the soil were analyzed according to four indicators of harmfulness, which were previously established based on the results of laboratory experiments to study the patterns of migration in the «soil - adjacent environments» system when justifying the MPCs.Results. It was established that the herbicides amicarbazone (chemical class – triazolones), bicyclopyrone (triketones), imazapyr and imazethapyr (imidazolinones) and the fungicides dimoxystrobin (strobilurins) and pydiflumetofen (pyrazole carboxamides) by the value of PIHI (3 points for each AS) and FIHI (from 7 to 11 points) do not require experimental establishment of the threshold concentration according to the air-migration indicator of harmfulness when justifying the MPCs. The organophosphorus fungicide iprobenfos according to the PIHI (5 points) was recognized as a candidate for the experimental study of migration in the «soil - atmospheric air» system; the value of FIHI (17 points) indicates the necessity of setting the threshold concentration of iprobenfos according to the air-migration harmful index.The results of experimental studies of migration in the «soil - adjacent environments» system proved the possibility and appropriateness of a scientifically based refusal to study the migration from soil to atmospheric air of amicarbazone, both imidazolinones, bicyclopyrone, dimoxystrobin and pidiflumetofen. At the same time, the necessity and obligation of experimental study of the behavior of iprobenfos in the «soil - atmospheric air» system was confirmed.Conclusions. Using the example of experimental substantiation of the medical and sanitary standard in the soil of 7 pesticides of different chemical classes, the reliability of the method of optimizing the volume of experimental studies when establishing the MPCs of AS PPP was proven by means of a scientifically justified refusal to study in the conditions of a laboratory experiment migration in the «soil - atmospheric air» system.
Keywords: herbicide; fungicide; soil; adjacent environments; migration; maximum permissible concentration